Evolution of toothbrushes throughout history - Lopez Beraun, Pablo Alonso (2025)
The toothbrush has evolved significantly throughout history, starting with the use of chewing sticks or miswak in ancient civilizations such as Babylon, around 3500-3000 BC. These sticks, derived from plants like Salvadora persica, have been used to this day in various parts of the world, especially in regions with limited access to modern dental products. The transition to more complex tools occurred with the invention of the first toothbrushes with handles and bristles during the Tang Dynasty in China (618-907 AD). Over the centuries, the design and materials of toothbrushes were refined, notably with the work of William Addis in 1780, who created the frst modern toothbrush with a bone handle and boar bristles. In the 20th century, advances in material technology, such as the introduction of nylon in 1938, replaced natural bristles with synthetic fibers that were more durable and easier to manufacture. Evolution continued with the development of electric toothbrushes in the 1930s, popularized in 1954, which facilitated their use for people with limited motor skills. Today, toothbrushes have incorporated features such as sustainability, increased effectiveness, and connectivity, marking the beginning of a new era in oral hygiene